2021
DOI: 10.1017/dmp.2021.54
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAPs) of Community Pharmacists Regarding COVID-19: A Cross-Sectional Survey in 2 Provinces of Pakistan

Abstract: The coronavirus disease 2019 (COVID-19) is a global pandemic having no therapy and pharmacists being a part of the healthcare system had a vital role in the management of COVID-19. The purpose of this study is to assess the knowledge, attitude, and practices (KAPs) of community pharmacists (CPs) regarding COVID-19. An online survey was conducted among 393 CPs in two provinces of Pakistan during the lockdown period. A validated questionnaire (Cronbach alpha, 0.745) was used for data collection. All statistical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 35 publications
14
44
0
2
Order By: Relevance
“…On the other hand, the finding of the present reviewed studies consistently showed that health professionals who were older, highly educated, and who had obtained information from social media, such as television, had good knowledge of COVID-19 compared to their counterparts (24). A possible explanation for this finding is the ability of highly educated health professionals to easily understand the nature of the disease and identify the sources of information.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, the finding of the present reviewed studies consistently showed that health professionals who were older, highly educated, and who had obtained information from social media, such as television, had good knowledge of COVID-19 compared to their counterparts (24). A possible explanation for this finding is the ability of highly educated health professionals to easily understand the nature of the disease and identify the sources of information.…”
Section: Discussionsupporting
confidence: 64%
“…The direction of the association of gender, service year, and taking infection prevention training were reported inconsistent among studies. Three studies reported that being female had a positive association with knowledge (20,23), while one study reported the opposite (24). In addition, being elder, having a higher level of education, and the use of social media as sources of information were factors found to be associated with better knowledge.…”
Section: Study Outcome Measuresmentioning
confidence: 93%
See 1 more Smart Citation
“…A questionnaire was designed from the published studies related to COVID-19 [9,[12][13][14][15][16][17][18].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Also, in low-middle income countries, deaths due to chronic diseases are a serious concern [3]. The mortality in low-middle income countries can be reduced by running public health programs where different stakeholders of the society participate to create awareness among the public about the myths of infectious and non-infectious diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%